2012
DOI: 10.1152/ajplung.00337.2011
|View full text |Cite
|
Sign up to set email alerts
|

CD40 amplifies Fas-mediated apoptosis: a mechanism contributing to emphysema

Abstract: . CD40 amplifies Fas-mediated apoptosis: a mechanism contributing to emphysema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…The existing evidence regarding PM and sCD40L mainly focuses on cardiovascular disease [37]. However, some studies have indicated that sCD40L plays a contributing role in pulmonary emphysema [38].…”
Section: Discussionmentioning
confidence: 99%
“…The existing evidence regarding PM and sCD40L mainly focuses on cardiovascular disease [37]. However, some studies have indicated that sCD40L plays a contributing role in pulmonary emphysema [38].…”
Section: Discussionmentioning
confidence: 99%
“…This was in accordance with the well-known hypothesis that depleting vascular endothelial growth factor induces the apoptosis of parenchymal epithelial and endothelial cells and results in emphysematous changes in COPD. 26 29 In contrast, air way inflammation in asthma is accompanied by vascular endothelial growth factor oversecretion and an increase in subepithelial microvessels. 30 Leakage from these immature microvessels enhances airway inflammation and hypersensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, alveolar epithelial cell inflammation and apoptosis are significant mechanisms in the pathobiology of CS-induced COPD (23,110). The deleterious components of cigarette smoke recruit macrophages, neutrophils, and T lymphocytes, which, in turn, aggravate air space enlargement and alveolar destruction, culminating in emphysematous inflammation (23).…”
Section: Key Studies and Recent Advances: A Literature Review From 20mentioning
confidence: 99%
“…IFN-␥ may be a useful indicator of COPD severity and, through mechanisms relatively unknown, play a role in initiating the immune response during virus-induced exacerbation. However, most importantly, through the stimulation of CD40, an important TNF receptor, IFN-␥ has been thought to induce the Fas-apoptotic pathway in epithelial cells and stimulate the enlargement of emphysematous airways (110). In addition, extracellular adenosine is often increased during tissue injury and inflammatory insults by the stimulation of ectonucleotidases, CD39 and CD73, or by variations in the activity and expression of adenosine deaminase (76).…”
Section: Key Studies and Recent Advances: A Literature Review From 20mentioning
confidence: 99%